Outcomes of Tongue Base Reduction and Lingual Tonsillectomy for Residual Pediatric Obstructive Sleep Apnea after Adenotonsillectomy - Ulualp,Seckin (2019)
Abstract Introduction Upper airway obstruction at multiple sites, including the velum, the oropharynx, the tongue base, the lingual tonsils, or the supraglottis, has been resulting in residual obstructive sleep apnea (OSA) after tonsillectomy and adenoidectomy (TA). The role of combined lingual tonsillectomy and tongue base volume reduction for treatment of OSA has not been studied in nonsyndromic children with residual OSA after TA. Objective To evaluate the outcomes of tongue base volume reduction and lingual tonsillectomy in children with residual OSA after TA. Methods A retrospective chart review was conducted to obtain information on history and physical examination, past medical history, findings of drug-induced sleep endoscopy (DISE), of polysomnography (PSG), and surgical management. Pre- and postoperative PSGs were evaluated to assess the resolution of OSA and to determine the improvement in the obstructive apnea-hypopnea index (oAHI) before and after the surgery. Results A total of 10 children (5 male, 5 female, age range: 10-17 years old, mean age: 14.5 ± 2.6 years old) underwent tongue base reduction and lingual tonsillectomy. Drug-induced sleep endoscopy (DISE) revealed airway obstruction due to posterior displacement of the tongue and to the hypertrophy of the lingual tonsils. All of the patients reported subjective improvement in the OSA symptoms. All of the patients had improvement in the oAHI. The postoperative oAHI was lower than the preoperative oAHI (p < 0.002). The postoperative apnea-hypopnea index during rapid eye movement sleep (REM-AHI) was lower than the preoperative REM-AHI (p = 0.004). Obstructive sleep apnea was resolved in children with normal weight. Overweight and obese children had residual OSA. Nonsyndromic children had resolution of OSA or mild OSA after the surgery. Conclusions Tongue base reduction and lingual tonsillectomy resulted in subjective and objective improvement of OSA in children with airway obstruction due to posterior displacement of the tongue and to hypertrophy of the lingual tonsils.